2016
DOI: 10.5625/lar.2016.32.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of hematology, biochemistry, and blood type in cynomolgus monkeys from cambodia origin

Abstract: Cynomolgus monkeys as nonhuman primates are valuable animal models because they have a high level of human gene homology. There are many reference values for hematology and biochemistry of Cynomolgus monkeys that are needed for proper clinical diagnosis and biomedical research conduct. The body weight information and blood type are also key success factors in allogeneic or xenogeneic models. Moreover, the biological parameters could be different according to the origin of the Cynomolgus monkey. However, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 23 publications
7
47
0
1
Order By: Relevance
“…2). Further, the mean concentration of hemoglobin in the anti-CD154 group was lower than the lower limit of the reference interval of platelets (reference interval of hemoglobin: 10.10–15.45 g/dl, calculated from a previous study 26 ).
Figure 2Comparison of hemoglobin level, platelet count, and soluble CD40L level, in cynomolgus monkeys with collagen-induced arthritis. Graphs of hemoglobin levels, platelet counts, and soluble CD40L levels.
…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…2). Further, the mean concentration of hemoglobin in the anti-CD154 group was lower than the lower limit of the reference interval of platelets (reference interval of hemoglobin: 10.10–15.45 g/dl, calculated from a previous study 26 ).
Figure 2Comparison of hemoglobin level, platelet count, and soluble CD40L level, in cynomolgus monkeys with collagen-induced arthritis. Graphs of hemoglobin levels, platelet counts, and soluble CD40L levels.
…”
Section: Resultsmentioning
confidence: 83%
“…Platelet number was markedly decreased due to platelet clumps in RA4 and RA5, especially during the first 2 weeks after anti-CD154 antibody therapy, and platelet numbers of RA 4 and 5 were lower than the lower limit of the reference interval of platelets (215.6–600.6 × 10 9 /L) 26 (platelet numbers of RA 4: before treatment, week 7 post-immunization: 364 × 10 9 /L → after treatment, week 8 post-immunization: 194 × 10 9 /L and week 9 post-immunization: 57.8 × 10 9 /L and RA 5: before treatment, week 7: 596 × 10 9 /L → after treatment, week 8 post-immunization: 180 × 10 9 /L, week 9 post-immunization: 180 × 10 9 /L) (Fig. 2).…”
Section: Resultsmentioning
confidence: 96%
“…As is well‐known, basal reference values are not only important for monitoring the care and maintenance of NHPs used in biomedical research, but are also critical for evaluating normal physiological states and the effects of treatments and experimental tests . Indeed, reference values play a vital role in selecting healthy subjects for such research and in evaluating non‐clinical findings …”
Section: Introductionmentioning
confidence: 99%
“…Chemical restriction or subjection, in particular, reduces stress in animals while increasing safety and improving the quality of the samples obtained . Many studies have reported the clinical effects of anesthesia on the physiological and biochemical parameters of NHPs . Research has shown that anesthetic drugs, and combinations thereof, produce secondary effects that can modify physiological responses by altering an animal's homeostasis, and cause such deleterious effects as hypotension, hypoxia, and hypothermia, among other disturbances, in anesthetized animals, and this can affect the results of research .…”
Section: Introductionmentioning
confidence: 99%
“…Identification of primate ABO blood groups is indispensable in many blood-related research fields, such as organ transplantation and hematology1. However, monkeys do not express ABH antigens on their red blood cells (RBCs)2, making the accurate determination of blood type difficult.…”
mentioning
confidence: 99%